The Successful Treatment of a Case of Linear Psoriasis with Ixekizumab - Ghoneim, Sara (Case Rep Dermatol Med, 2017)
Linear psoriasis is an unusual clinical variation of psoriasis that manifests segmentally along the lines of Blaschko. A major differential diagnosis is inflammatory linear verrucous epidermal nevus (ILVEN). The treatment of linear psoriasis is often challenging, with inadequate response to biological agents reported in the literature. We report a case of a 25-year-old African-American female who presented with asymptomatic hyperkeratotic papules along the lines of Blaschko and was subsequently diagnosed with linear psoriasis. After failing conventional treatment regimens, the patient received a trial of ixekizumab with complete resolution of cutaneous lesions reported after 4 months and only 8 doses of the anti-IL-17 biologic agent.